Profile of Analytical Thinking Skills Through Inquiry-Based Learning in Science Subjects - Alifia Suryatin Ramadani; Zainul Arifin Imam Supardi; Tukiran; Eko Hariyono (Indonesia Approach Education, 2021)
The 2013 curriculum aims to form students who are ready to face the 21st century so that the 2013 curriculum is not only taught about aspects of knowledge but also aspects of skills. Thinking skills are the skills used in the 2013 curriculum, where one of the thinking skills students need is expertise in analytical thinking. These skills are necessary for science learning. Analytical thinking skills can be improved if the teacher trains them correctly, both from the learning model and learning strategies. This study examines learning models and learning tools that can improve analytical thinking skills. Learning based on inquiry learning is expected to improve students' analytical thinking skills. The findings of this study, it is known that inquiry-based models and tools can improve analytical thinking skills because they start from a problem. The problems given are then discussed with the group to find information that fits the situation and find ways to solve the problem nicely by conducting experiments or observations, then summing up the results obtained and communicating them well. Analytical thinking skills are closely related to problem-solving. So with analytical thinking skills, students will quickly identify and solve a problem.